Tail risk and extreme events: Connections between oil and clean energy - Elisa Di Febo; Matteo Foglia; Eliana Angelini (Risks, 2021)
Do tail events in the oil market trigger extreme responses by the clean-energy financial market (and vice versa)? This paper investigates the relationship between oil price and clean-energy stock with a novel methodology, namely extreme events study. The aim is to investigate an asymmetry effect between the response to good versus bad days. The results show how the two markets influence each other more negatively, i.e., extreme negative events significantly impact the other market. Furthermore, we document how the impact of the shock transmitted by oil prices to clean-energy stocks is less than the amount of shock transmitted oppositely. These findings have important implications for investor and renewable energy policies.
Keywords: 330; extreme events study; oil price; renewable energy stock; tail risk